1999
DOI: 10.1103/physrevlett.83.2014
|View full text |Cite
|
Sign up to set email alerts
|

From Band Insulator to Mott Insulator in One Dimension

Abstract: We derive the phase diagram for the one-dimensional model of a ferroelectric perovskite recently introduced by Egami, Ishihara and Tachiki [Science, 261, 1307[Science, 261, (1993]. We show that the interplay between covalency, ionicity and strong correlations results in a spontaneously dimerized phase which separates the weak-coupling band insulator from the strongcoupling Mott insulator. The transition from the band insulator to the dimerized phase is identified as an Ising critical point. The charge gap va… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

23
315
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 202 publications
(340 citation statements)
references
References 17 publications
23
315
2
Order By: Relevance
“…On the other hand, up to irrelevant corrections, H AT in (19) transforms to the marginal interaction terms in (2) with g = 8Ka 0 . The correspondence between theh-terms in (11) and (9) is self-evident. Thus, we have shown that, in the weak-coupling limit (20), the 1D quantum model (11) can be regarded as a symmetry preserving lattice counterpart of the continuum theory (9).…”
Section: Introductionmentioning
confidence: 96%
See 4 more Smart Citations
“…On the other hand, up to irrelevant corrections, H AT in (19) transforms to the marginal interaction terms in (2) with g = 8Ka 0 . The correspondence between theh-terms in (11) and (9) is self-evident. Thus, we have shown that, in the weak-coupling limit (20), the 1D quantum model (11) can be regarded as a symmetry preserving lattice counterpart of the continuum theory (9).…”
Section: Introductionmentioning
confidence: 96%
“…The correspondence between theh-terms in (11) and (9) is self-evident. Thus, we have shown that, in the weak-coupling limit (20), the 1D quantum model (11) can be regarded as a symmetry preserving lattice counterpart of the continuum theory (9). General universality considerations allow us to expect that, if the field-theoretical model (9) displays a certain quantum critical behavior, this should also be a property of the quantum lattice model (11) even when its parameters are not restricted by the condition (20).…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations